VALUE CHAIN OF SWEET POTATOES IN AGLOEMERATION AREAS MEDAN AND DELI SERDANG - Akbar Habib; Jabal Tarik Ibrahim; Aris Winaya; Sabrina (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
ObjectiveThis research is to analyze the actors involved in the value chain and marketing flow of sweet potatoes in the Medan and Deli Serdang agglomeration areas. Analyzing the performance of the sweet potato commodity value chain from upstream to downstream in the cities of Medan and Deli Serdang. Identifying the sweet potato commodity value chain in Deli Serdang Regency. Value chain analysis is carried out by first identifying the actors involved in the sweet potato value chain and the activities carried out. Value chain analysis was carried out by looking at the primary and secondary activities of each institution involved in the sweet potato value chain in the Deli Serdang area. Measuring value chain performance uses financial analysis by first calculating production costs, income, production and receipts as well as share margins for each actor. The results of this research are that the actors involved in sweet potato marketing activities in Deli Serdang Regency start from farmers, collectors, wholesalers, retailers and final consumers (Home Industry), each of whom in the value chain gets different benefits.